Tax provisioning by extractive industry multinational subsidiaries - Khanindra Ch. Das (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Extractive industries are spread across mining of metal and minerals, oil and gas, among others. Multinationals in these sectors are confronted with different challenges ranging from corruption, political risk, economic uncertainty, sunk costs, and the long-gestation periods to execute projects. As a result, tax payment behaviour of subsidiaries in the extractive sector could be dependent not only on these factors, but also on the life cycle of the subsidiary, profitability, and holding structure. Furthermore, emerging economy multinationals in the extractive industries could be state-owned and may invest in foreign subsidiaries for strategic reasons. We examine tax provision in host countries by India's multinational subsidiaries in the extractive industry. Panel data analysis is carried out for the period 2010-20. It is found that tax provision remains lower in the initial years of subsidiary life and increases with the sustenance of subsidiary in the host country for a longer period. In addition, subsidiaries of public sector enterprises are found to have higher tax provisions than their private counterparts. When it comes to the determinants, economic policy uncertainty, corruption, and political stability are found to significantly affect tax provision.
Keywords: F23; H26; Q34; 330; extractive sector; tax provision; economic policy uncertainty; corruption; political stability; public sector